Estabilidade e qualidade do farelo de arroz sob diferentes tratamentos e aplicação do produto extrusado em biscoito - LACERDA, Diracy Betânia Cavalcante Lemos (2008)
Rice bran is a by product of the rice milling process. It corresponds to 8% of the total rice grain and is used as feed and fertilizer mainly. The major problem related to its use in human nutrition is the rancification process starting soon after its extraction. The objective of this work was to evaluate the stability of raw rice bran (RRB), extruded rice bran (ERB) and rice bran obtained after parboilization (RBP) when stored at room temperature for 180 days in polyethylene bags as well as to characterize them and the cookies formulated with ERB. Physicochemical, microbiological and stability tests (lipase activity, hydrolytic rancidity and peroxide index) were performed on rice bran from cultivar Primavera (donated by benefited industry) and on the prepared cookies with ERB using a completely randomized design, with a control and four treatments (12.5%, 25%, 37.5% and 50% of ERB). All tests were performed according to standard methodologies. PRB presented the highest contents of protein (17.7 g 100 g-1), lipid (36.03 g 100 g-1), dietary fibers (34.06 g 100 g-1), calcium (99.45 mg 100g-1), zinc (15.58 g 100 g-1), copper (1.45 g 100 g-1) and manganese (17.81 g 100 g-1) and the lowest contents of carbohydrates (5,73 g 100 g-1), ashes (7.01 g 100 g-1) and iron (6.83 mg 100 g-1). Lipase activity and hydrolytic rancidity were higher in NRB during the storage period but the peroxidase index was lower. Cookies were well accepted and did not show any significant diference regarding appearance, texture and flavor. Cookies with 50% of ERB had higher contents of protein (18.9%), dietary fiber (213.3%) and ashes (59.1%) than the control. Forty grams of that formulation supplies more than 10% of daily recommended intakes of magnesium, phosphorus and copper. Cookies also presented acceptable microbiological standards according to Brazilian legislation. Extrusion and parboilization are efficient methods to prevent free fatty acid formation in ERB and PRB, placed in plastic films permeable to oxygen and stored at room temperature, but they contributed to higher concentrations of peroxides in those rice bran. Cookies with 50% ERB had a better nutritional quality than those without rice bran